All-Trans Retinoic Acid-Induced Pseudotumor Cerebri during Induction Therapy for Acute Promyelocytic Leukemia: A Case Report and Literature Review. (3rd June 2012) - Holmes, Dylan; Vishnu, Prakash; Dorer, Russell K.; Aboulafia, David M.
Abstract : All-trans retinoic acid (ATRA), a derivative of vitamin A, is an essential component in the treatment of acute promyelocytic leukemia (APL). Though considered to be a relatively safe drug, use of ATRA can lead to several side effects such as retinoic acid syndrome and pseudotumor cerebri (PC). PC is a rare disorder characterized by neurologic and ocular signs and symptoms of increased intracranial pressure, but with normal cerebrospinal fluid composition and normal brain imaging. Most of the previous studies suggest that PC, as a complication of ATRA therapy, occurs predominantly in the pediatric age group. Herein, we report a rare case of ATRA-induced PC in a 38-year-old woman undergoing induction treatment for APL. Symptoms improved with discontinuation of ATRA and treatment with acetazolamide. Concomitant administration of medications such as triazole antifungals which influence the cytochrome P-450 system can exacerbate this potential complication of ATRA. In this paper, we also review the current literature, provide a descriptive analysis of clinical features, and discuss the principles of management of ATRA-induced PC.